Physical activity and healthy lifestyle in Canarian teenagers - Navarro Valdivielso, Manuel; Ojeda García, Roberto; Navarro Hernández, Miriam; López López, Eduardo; Brito Ojeda, Estrella; Ruiz Caballero, José Antonio (FEADEF, 2012)
The present study about adolescent from the Canary Islands, evidence that a minority of adolescents follow the guidelines or recommendations for physical activity, showing low level of physical activity of moderate intensity and vigorous, levels which are shown away from the established recommendations for this group of age, and insufficient to attain the positive effects arising from the practice of physical activity, and these low levels are more accentuated in girls than in boys. These evidences, justify, the need to change this trend and promote substantial changes in practice habits of physical activity of children and adolescents. To ensure this change, are shown as very adequate, the implementation of physical education programs out of the school schedule, along with the necessary increase in teaching hours which now is assigned to physical education in the current curriculum of Basic Education